Effect of Exogenous Melatonin on Antioxidant Enzyme Activity in Kiwifruit Hayward under Salt Stress. Issue 5 (February 2019) - Liu, Xinling; Xia, Hui; Yuan, Xuezhen; Lv, Xiulan; Liang, Dong
Abstract: In order to explore the effect of exogenous melatonin (MT) on antioxidant enzyme activity in kiwi under the salt stress, Hayward seedlings primed with 0.1μmolL −1 MT were used as the experimental materials and treated with 100 mmol L −1 NaCl in hydroponic condition. The results showed that exogenous MT had certain effect on the activity of SOD, POD during the early stage of salt stress, but the effect was not significant.